Loss Analysis in Accordance Switching State of 3kW Full-bridge Converter with Current Doubler Rectifier - Park, Je-Suk; Park, Young-Un; Shin, Duck-Shick; Kim, Dae-Kyong (International Journal of Engineering and Technology, 2018)
Background/Objectives: The losses mostly dissipate to the thermal and reduce the output efficiency of the power conversion system.Methods/Statistical analysis: loss analysis of the 3kW DC-DC converter in accordance switching state through thermal module of circuit analysis tool.Findings: Loss analysis of a DC-DC converter was performed using the thermal module function of circuit analysis tool. Loss of power semiconductor is analyzed by modeling power semiconductor device for loss analysis with device database editor.Improvements/Applications: The thermal of power semiconductors analyzes the thermal by adding a thermal equivalent resistor to the device for power semiconductor loss analysis. The results are expected to be helpful for heat dissipation design. Future research will add inductor loss analysis.Â Â